2020
DOI: 10.5093/jwop2020a16
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Role of Personal Resources in Perceived Employability of Young People in Different Labor Conditions

Abstract: Personal resources and labor market are factors that contribute to perceived employability. However, how changing labor market conditions affect the relationship between personal resources like career enhancing strategies, personal initiative, and career passivity with self-perceived employability remains unclear. Recent events in Spain give an opportunity to examine if personal resources predict perceived employability differently during normal and harsh labor conditions. Two representative samples of young p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
4
1
Order By: Relevance
“…Previous studies have hinted that positive personal resources predict perceived employability in normal labour market conditions only (e.g. Low et al, 2020). However, despite the cross-sectional nature of this current study, the findings hint that the predictive role of positive personal resources also applies during times of challenging job markets (e.g.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have hinted that positive personal resources predict perceived employability in normal labour market conditions only (e.g. Low et al, 2020). However, despite the cross-sectional nature of this current study, the findings hint that the predictive role of positive personal resources also applies during times of challenging job markets (e.g.…”
Section: Discussioncontrasting
confidence: 85%
“…Career counsellors need to be aware that the Covid-19 pandemic has increased competition for graduate jobs and negatively impacted perceptions of employability in students. Supporting students by preparing them for the graduate labour market and enhancing their own perceptions of employability can benefit the individual, the university, employers and play a crucial role in facilitating economic recovery (Low et al, 2020). This might include positive messaging, working with local employers to source jobs for students or helping students to adapt to new methods of virtual assessment for securing employment.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…This paper provides a systematic review of empirical evidence on the characteristics and effectiveness of interventions to support dyslexic adults' personal resources. Self-regulatory skills, self-efficacy, and the ability to employ self-control strategies when distressed or challenged are key to high employability [56]. Yet, dyslexic adults may score lower on such personal resources compared to other employees because of cognitive impairment and negative self-perceptions related to it [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Social capital conceptually underpins the construct of employability [47]. Employability is the sub-dimension of adaptability that originates through socially fit gigs [48]. Based on a comprehensive meta-analysis of 107 reports, Safavi and Bouzari concluded that perceived employability is complemented by social capital, ending in subjective career achievement joys [49].…”
Section: The Mediating Role Of Perceived Employabilitymentioning
confidence: 99%